Mental stress of lay family caregivers - Jedlinská, Martina; Hlúbik, Pavol; Levová, Jana (Profese Online, 2009)
The submitted study deals with health problems and their global promotion with focus on mental health concretly applied to lay family caregivers. The main aim of the research is an assessment of their mental stress together with the possibilities which could reduce it and so contribute to its prevention. For research has been adopted questionnaire method which proved increased mental stress in lay family caregivers.
Keywords: mental stress; lay family carers; social support; questionnaire Burnout Measure